2020
DOI: 10.1017/ice.2020.375
|View full text |Cite
|
Sign up to set email alerts
|

Using diagnostic stewardship to reduce rates, healthcare expenditures and accurately identify cases of hospital-onset Clostridioides difficile infection

Abstract: Objective: Lack of judicious testing can result in the incorrect diagnosis of Clostridioides difficile infection (CDI), unnecessary CDI treatment, increased costs and falsely augmented hospital-acquired infection (HAI) rates. We evaluated facility-wide interventions used at the VA San Diego Healthcare System (VASDHS) to reduce healthcare-onset, healthcare-facility–associated CDI (HO-HCFA CDI), including the use of diagnostic stewardship with test ordering criteria. Design: We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…7 In this population, CDI accounts for just 10%-20% of cases of diarrhea, whereas medications, including promotility agents, antimicrobials, and tube feeding account for the overwhelming majority. 8 Due to highly sensitive NAAT that cannot distinguish colonization from infection, restricting testing to patients with no alternative causes for diarrhea is essential in preventing inappropriate diagnosis of CDI and overtreatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In this population, CDI accounts for just 10%-20% of cases of diarrhea, whereas medications, including promotility agents, antimicrobials, and tube feeding account for the overwhelming majority. 8 Due to highly sensitive NAAT that cannot distinguish colonization from infection, restricting testing to patients with no alternative causes for diarrhea is essential in preventing inappropriate diagnosis of CDI and overtreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic stewardship is an effective strategy for reducing inappropriate C. difficile testing in inpatient settings. [8][9][10] Soft stops, such as clinical decision support algorithms and best practice alerts (BPAs), are commonly used to mitigate unnecessary testing, especially in the setting of promotility agents. However, hard stops that actively block orders are underutilized despite being more effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic stewardship of C. difficile testing has become increasingly important as clinicians attempt to optimize NAAT testing to reduce inappropriate diagnoses, unnecessary treatment, and facility HAI rates. 19,20 Trends in C. difficile testing should be monitored because focus on diagnostic stewardship for C. difficile testing has increased. Further study is needed to assess appropriateness of C. difficile testing during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 A third potential explanation for the decline we observed in HO-CDI rates relates to implementation of better diagnostic stewardship by the health care facilities in our cohort. 35 Solanky et al 36 showed that diagnostic stewardship had the most substantial association with reductions in HO-CDI rates among other interventions, including prompt isolation of patients with CDI, optimal environmental cleaning, hand hygiene, fluoroquinolone and proton-pump inhibitor stewardship, and the rejection of solid stool samples by the laboratory. Several other studies that used diagnostic stewardship interventions significantly reduced unnecessary testing using a variety of approaches, such as health care professional education, decision-making algorithms, and the deployment of what are known as hard stops requiring a specialist consultation or laboratory approval prior to test ordering.…”
Section: Discussionmentioning
confidence: 99%